RTK metoda GPS-izmere - Stopar, Bojan (Geodetski vestnik, 1997)
The RTK method of GPS measurements has become a very useful tool for different geodetic tasks in which positioning is required. This method sucessfully replaces tachimetric measurements in topographic and cadastral surveys; it has also proved to be useful in numerous technical works within the scope of geodetic engineering. The advantage of the RTK method is mainly in acquiring data on position and data on positional accuracy in the field, which is an advantage in comparison with other methods of GPS measurement. Like other methods of GPS measurement, the RTK method suffers from a weakness which can be avoided only by combining it with terrestial topographic measurement. Real topographic-cadastral surveys performed with the use of the RTK method are presented and their efficiency is compared with the terrestial topographic surveys.
Keywords: geodezija; GPS; izmera; metode; topografija